A review of risk concepts and models for predicting the risk of primary stroke - Hunter, Elizabeth; Kelleher, John D. (Frontiers in Neuroinformatics, 2022)
Predicting an individual's risk of primary stroke is an important tool that can help to lower the burden of stroke for both the individual and society. There are a number of risk models and risk scores in existence but no review or classification designed to help the reader better understand how models differ and the reasoning behind these differences. In this paper we review the existing literature on primary stroke risk prediction models. From our literature review we identify key similarities and differences in the existing models. We find that models can differ in a number of ways, including the event type, the type of analysis, the model type and the time horizon. Based on these similarities and differences we have created a set of questions and a system to help answer those questions that modellers and readers alike can use to help classify and better understand the existing models as well as help to make necessary decisions when creating a new model.